Diethylhexyl phthalate exposure amplifies oxidant and inflammatory response in fetal hyperglycemia model predisposing insulin resistance in zebrafish embryos - Kaplan, Gül; Beler, Merih; Ünal, İsmail; Karagöz, Atakan; Eğilmezer, Gizem; Üstündağ, Ünsal Veli; Cansız, Derya; Alturfan, Ahmet Ata; Emekli Alturfan, Ebru (My University, 2024)
Exposure of zebrafish embryos to glucose is a suitable model for the fetal hyperglycemia seen in gestational diabetes. Diethylhexyl phthalate (DEHP), which is considered an endocrine-disrupting chemical, is one of the most common phthalate derivatives used in stretching plastic and is encountered in every area where plastic is used in daily life. In the present study, the effects of DEHP on pathways related to insulin resistance and obesity were examined in zebrafish embryos exposed to glucose as a fetal hyperglycemia model. Zebrafish embryos were exposed to DEHP, glucose, and glucose + DEHP for 72 h post-fertilization (hpf), and developmental parameters and locomotor activities were monitored. At 72 hpf ins, lepa, ppar?, atf4a, and il-6 expressions were determined by RT-PCR. Glucose, lipid peroxidation (LPO), nitric oxide (NO) levels, glutathione S-transferase (GST), superoxide dismutase (SOD), and acetylcholine esterase (AChE) activities were measured spectrophotometrically. Compared with the control group, glucose, LPO, GST activity, il6, and atf4a expressions increased in all exposure groups, while body length, locomotor, and SOD activities decreased. While AChE activity decreased in the DEHP and glucose groups, it increased in the glucose + DEHP group. Although glucose exposure increased ppar? and lepa expressions, DEHP significantly decreased the expressions of ppar? and lepa both in the DEHP and glucose + DEHP groups. Our findings showed that DEHP amplified oxidant and inflammatory responses in this fetal hyperglycemia model, predisposing insulin resistance in zebrafish embryos.
Keywords: Diethylhexyl Phthalate; Fetal Hyperglycemia; Insulin Resistance; Zebrafish Embryos